2015
DOI: 10.1016/j.psychsport.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Advancing theory and application of cognitive research in sport: Using representative tasks to explain and predict skilled anticipation, decision-making, and option-generation behavior

Abstract: Please cite this article as: Belling, P.K., Suss, J., Ward, P., Advancing theory and application of cognitive research in sport: Using representative tasks to explain and predict skilled anticipation, decision-making, and option-generation behavior,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
7
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 38 publications
7
59
7
5
Order By: Relevance
“…Although this may be useful for substantiating claims regarding cognitive predictors of performance at this level in these types of domains, it would be highly beneficial to compare the current data with that of a highly-skilled sample. In this cohort, we predict that anticipation skill would contribute more to skilled performance on the soccer recognition test, in line with previous work (e.g., Belling, Suss, & Ward, 2013). Direct comparison between experts and initiates/novices in future work is certainly needed to test this prediction.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although this may be useful for substantiating claims regarding cognitive predictors of performance at this level in these types of domains, it would be highly beneficial to compare the current data with that of a highly-skilled sample. In this cohort, we predict that anticipation skill would contribute more to skilled performance on the soccer recognition test, in line with previous work (e.g., Belling, Suss, & Ward, 2013). Direct comparison between experts and initiates/novices in future work is certainly needed to test this prediction.…”
Section: Discussionsupporting
confidence: 87%
“…We learned another important lesson within complex and dynamic domains: Although tools such as the OASSIS may still be the best means of predicting skill among experts (see Belling, Suss, & Ward, 2013), it is important to determine the boundaries for effective use of these tools before applying them to all skill levels. We also acknowledge the limitations of this research.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to "read the game" is crucial in team sports. Expert players can anticipate upcoming moves (Gabbett, Rubinoff, Thorburn & Farrow, 2007;Ward & Williams, 2003;Williams & Davids, 1995), assess game situations (Belling, Suss, & Ward, 2015;Ward, Ericsson, & Williams, 2013), and make decisions accurately and efficiently (Vaeyens, Lenoir, Williams, Mazyn & Philippaerts, 2007). Such perceptual-cognitive skills are amongst the better predictors of skill level in sport (Mann, Williams, Ward & Janelle, 2007;Ward & Williams, 2003).…”
Section: Informational Constraintmentioning
confidence: 99%
“…Several studies have examined skill-based differences in anticipation using a temporal occlusion method in team sports (e.g., Belling et al, 2015;Ward et al, 2013). These studies demonstrated that skill-based differences in the ability to anticipate the outcome of a pattern of play are more apparent when access to situational information is constrained (e.g., occluded earlier in the play sequence).…”
Section: Informational Constraintmentioning
confidence: 99%
“…In many real-life situations, decisions have to be made under limited time, and it is known that adults adapt to time limitation using faster and simpler (Ben Zur & Brenitz, 1981;Payne, Bettmann, & Johnson, 1988), but not necessarily more effective (Belling, Suss, & Ward, 2015) strategies. Recent work has shown that children are ecological learnersthey modify their learning strategies to the characteristics of the task at hand (Horn, Ruggeri, & Pachur, 2016;Nelson, Divjak, Gudmundsdottir, Martignon, & Meder, 2014;Ruggeri & Lombrozo, 2015), and they do so already by age 4 (Ruggeri, Sim, & Xu, 2017).…”
Section: Time-limitation Effectsmentioning
confidence: 99%